2020
DOI: 10.21873/invivo.12194
|View full text |Cite
|
Sign up to set email alerts
|

Giant Intrathoracic Schwannoma: A Case Report

Abstract: Background/Aim: Thoracic neurogenic tumors are most frequently located in the posterior part of the mediastinum or on the chest wall, along the intercostal nerves. Schwannomas are very well tolerated for a long period, until the tumor reaches a large size and compression of the neighbouring mediastinal organs, chest wall or spine appears. The purpose of this article was to present a case of a giant right forth intercostal nerve Schwannoma, completely resected by a right antero-lateral thoracotomy. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Some authors consider that the most common primary pleural tumors are solitary pleural fibromas; however, leiomyoma must be included as an option during the differential diagnosis, even though it is a rare pathology (35). In fact, during the differential diagnosis other types of tumors should also be taken into consideration, such as neuromas, secondary lesions or other intrapleural tumoral masses (36,37). In our case, we chose a cautious intraoperative approach using a wide resection with oncological margins, as if we were removing a solitary pleural fibroma.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors consider that the most common primary pleural tumors are solitary pleural fibromas; however, leiomyoma must be included as an option during the differential diagnosis, even though it is a rare pathology (35). In fact, during the differential diagnosis other types of tumors should also be taken into consideration, such as neuromas, secondary lesions or other intrapleural tumoral masses (36,37). In our case, we chose a cautious intraoperative approach using a wide resection with oncological margins, as if we were removing a solitary pleural fibroma.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies revealed that 16% of SCLC tumors and 10% of low-grade neuroendocrine subtypes lose their expression of neuroendocrine markers: ASCL1, NeuroD1 and NKx2-1. This loss of neuroendocrine expression results in major morphology modifications such as growth characteristics, with major clinical implications (53,54). Glucose transfer transporter 1 (GLUT-1) is a protein that helps in the process of glucose transport, found in increased levels in all types of neuroendocrine cancers, indicating an HG-LNET (10).…”
Section: Biological Landscape Of Lung Neuroendocrine Tumors (Lnets)mentioning
confidence: 99%
“…Due to compression or invasion of the surrounding tissues, neurogenic symptoms, back pain, or difficulty swallowing can also be observed ( 7 , 13 ). Apically located mediastinal masses may cause superior vena cava syndrome due to the compression ( 14 ).…”
Section: Discussionmentioning
confidence: 99%